Síndrome de sobrecarga en cuidadores de personas con Discapacidad Física en el Centro de Salud de San Miguel, provincia Bolívar, período 2019 - Alvarez Zurita, Jessica Leonor (2019)
The objective of the present investigation was to determine the risk factors associated with overload syndrome in caregivers of people with physical disabilities. It addresses a problem little studied in the local context that directly affects the informal carers in charge of people with disabilities that require permanent care. The study is framed in a transversal and field type. We worked with the entire study population, 70 people who work as informal caregivers of people with moderate and severe physical disability who go to the San Miguel de Bolívar Health Center. The variables measured were the risk factors and the level of overload; for which the Zarit Test was applied, which is a series of 22 questions which had an assessment that goes from 0-4 points, and, for the establishment of the risk factors, a questionnaire was developed. The presentation of the results was done through the application of descriptive statistical techniques, and hypothesis testing through the application of Chi square. The main results found were 5% (4 people) presented Absence of overload, 32% (22 people) Light overload and 63% (44 people) Overload Intense. Regarding the characteristics, Gender, Civil Status, Degree of Schooling, Relationship, Time in years, Time in days per week, Time in hours per day and the Percentage of Disability of the person in their care, as the main ones were identified. Risk factors for presenting or not overload syndrome. It was concluded that the presence of overload is associated with the sociodemographic factors identified in the research, so the Care Proposal is made for caregivers of people with physical disabilities who come to the Health Center of San Miguel de Bolívar, Ecuador. KEY WORDS: Overload syndrome, risk factors, physical disability.